2022
DOI: 10.1017/s0033291722003154
|View full text |Cite
|
Sign up to set email alerts
|

The role of daily adjustment disorder, depression and anxiety symptoms for the physical activity of cardiac patients

Abstract: Background Physical activity (PA) is crucial in the treatment of cardiac disease. There is a high prevalence of stress-response and affective disorders among cardiac patients, which might be negatively associated with their PA. This study aimed at investigating daily differential associations of International Classification of Diseases (ICD)-11 adjustment disorder, depression and anxiety symptoms with PA and sedentary behaviour (SB) during and right after inpatient cardiac rehabilitation. Met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Recently, Bermudez et al (2021) showed that next to the sociocognitive factors of the theory of planned behavior (Ajzen, 2006), affective and implicit attitudes, as well as structural and intercomponential ambivalence could explain physical activity patterns of patients with cardiac disease. Therefore, endorsing and incorporating affective processes could be a valuable further development for the HAPA and should be part of future studies in the domain of physical activity (Bermudez et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Bermudez et al (2021) showed that next to the sociocognitive factors of the theory of planned behavior (Ajzen, 2006), affective and implicit attitudes, as well as structural and intercomponential ambivalence could explain physical activity patterns of patients with cardiac disease. Therefore, endorsing and incorporating affective processes could be a valuable further development for the HAPA and should be part of future studies in the domain of physical activity (Bermudez et al, 2022).…”
Section: Discussionmentioning
confidence: 99%